Feeling Right About How You Play: The Effects of Regulatory Fit in Games for Learning. (July 2013) - Lee, Yu-Hao; Heeter, Carrie; Magerko, Brian; Medler, Ben
Serious games are often assigned to learners and not played voluntarily. A problem for educators is how to motivate learners in these assigned conditions. This study examines the influence of regulatory fit experience on player motivations and time spent on learning aspects of the game. Regulatory fit theory posits that when instructions match the learners' promotion or prevention motivational systems, learners will experience "regulatory fit, " which will make them "feel right" about the current instructions and tasks. Our findings support the regulatory fit theory. When learners experienced regulatory fit, they played the game for 26% longer time than learners who did not experience regulatory fit. Learners in regulatory fit conditions also displayed more learning-related behaviors such as spending more time on learning feedback both during gameplay and between gameplay sessions. Positive feedback seems to motivate promotion-oriented learners; however, negative feedback did not demotivate prevention-oriented learners as theory predicted.